PENYIMPANGAN SOSIAL DALAM NOVEL HATI YANG BERCAHAYA KARYA WIWID PRASETYO - Leni Marlina; Bakhtaruddin Nasution; Muhammad Ismail Nasution (Faculty of Languages and Arts, Universitas Negeri Padang, 2013)
The study aims to describe'' (1) social distortion against the prevailing norms in society contained in novel The glowing hearts by Prasetyo Wiwid, (2) The causes of social deviation in novel The glowing hearts by Prasetyo Wiwid, (3) The causes of irregularities contained in novel The glowing hearts Prasetyo Wiwid work. This research is a qualitative research which used descriptive method and used mimesis approach, to see how the social equation in the novel The glowing hearts by Prasetyo Wiwid, the research was done by analyzing the novel by describing the structure of the novel, classifying the deviated event by each character and finally made the conclusion.